Parque lineal Ciudad del viento en Bogotá (2021)
The city of Bogotá, like other large cities in the world, constantly generates housing problems, caused mainly by the natural population increase and the displacement of the population from smaller cities. The concentration of inhabitants in this city causes an increase in transportation time, a demerit in the quality of housing and mainly the ecological deterioration of the city due to the pollution that occurs and is generating a deterioration in the environment, or also with new construction projects or buildings that in one way or another can have a significant impact on the environment. For this reason, it is very necessary to have ecological scenarios that help to combat this daily pollution, thus the ecological parks arise. The demand for housing and the lack of space are reflected in problems of a social nature such as the lack of integration of families. This project aims to propose some sustainability criteria to the current city model with the approach of an urban proposal for landscape design in an area in which the diagnosis was carried out in order to interpret the environmental conditions in which it is found, and thus develop a proposal that involves the recovery of the sector by creating an ecological park that restores the lost environmental quality. Tours will also be involved looking for spaces for contemplation, permanence, rest, reading areas and multiple activity areas, linked to the proposed architectural project; which in this case are five modules, which respond to the interest of covering the deficit of social, cultural, recreational, sports and educational facilities, since in the locality there is a large concentration of low and middle stratum that has little grouping of institutions public academics which need this local complement.